"Y(s)=L(y)=\\int\\limits_0^\\infty e^{-st}y(t)\\,dt.\\\\\nL(y'')=-3-3\\cdot s + s^2\\cdot \\int\\limits_0^\\infty e^{-st}y(t)\\,dt=\\\\\n=-3-3\\cdot s + s^2\\cdot Y(s).\\\\\n L(f(t))=\\int\\limits_0^\\infty e^{-st}f(t)\\,dt=\\int\\limits_0^1 e^{-st}f(t)\\,dt+\\int\\limits_1^\\infty e^{-st}f(t)\\,dt=\\\\\n=\\int\\limits_0^1 e^{-st}t\\,dt+\\int\\limits_1^\\infty e^{-st}\\,dt=\\frac{1-e^{-s}-se^{-s}}{s^2}+\n\\frac{e^{-s}}{s}.\\\\\\\\\n\n-3-3\\cdot s + s^2\\cdot Y(s)+4\\cdot Y(s)=\\frac{1-e^{-s}-se^{-s}}{s^2}+\n\\frac{e^{-s}}{s}\\\\\n(s^2+4)\\cdot Y(s)=3+3\\cdot s+\\frac{1-e^{-s}-se^{-s}}{s^2}+\n\\frac{e^{-s}}{s}\\\\\nY(s)=\\frac{3+3\\cdot s+\\frac{1-e^{-s}-se^{-s}}{s^2}+\n\\frac{e^{-s}}{s}}{s^2+4};"
Comments
Leave a comment